Frontiers in Electronic Technologies Trends and Challenges - Prabaharan, S.R.S.; Thalmann, Nadia Magnenat; Kanchana Bhaaskaran, V. S.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book is a collection of keynote lectures from international experts presented at International Conference on NextGen Electronic Technologies (ICNETS2-2016). ICNETS2 encompasses six symposia covering all aspects of electronics and communications domains, including relevant nano/micro materials and devices . This volume comprises of recent research in areas like computational signal processing analysis, intelligent embedded systems, nanoelectronic materials and devices, optical and microwave technologies, VLSI design: circuits systems and application, and wireless communication networks, and the internet of things. The contents of this book will be useful to researchers, professionals, and students working in the core areas of electronics and their applications, especially to signal processing, embedded systems, and networking.
Nadine: A Social Robot that can Localize Objects and Grasp them in a Human Way -- Data-Driven Analysis of Collections of Big Datasets by the Bi-Copam Method Yields Field-Specific Novel Insights -- Do You Mean What You Say? Recognizing Emotions in Spontaneous Speech -- Sensors and Actuators for HCI and VR: A Few Case Studies -- Frequency Conversion Layers for Si Solar Cell Efficiency Improvement -- Design and Fabrication of 320 × 256 Focal-Plane Array Using Straincoupled Quaternary Capped InAs/GaAs Quantum Dots Infrared Photo-Detectors for Thermal Imaging -- Metamaterial Based Planar Antennas -- An Overview on Memristor-Based Non-Volatile LUT of an FPGA -- Radio-Frequency Integrated Circuit Design -- Cyber Situational Awareness For CPS, 5G And IoT.
Keywords: Signal processing; Electronic circuits; Microtechnology; Microelectromechanical systems; Signal, Speech and Image Processing; Electronic Circuits and Systems; Microsystems and MEMS